Application of the Problem Based Learning (PBL) Learning Model to Improve Mathematics Learning Outcomes Material Multiplication of Whole Numbers Class III UPTD SDN 192 Barru - Syamsinar, Syamsinar; Nurapidah, Nurapidah; Nasharuddin, Nasharuddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This journal reviews the material on multiplication of whole numbers for class III of UPTD SDN 192 Barru. This study aims to determine the material on multiplication of whole numbers in the mathematics learning process in class III of UPTD SDN 192 Barru. This type of research is classroom action research (PTK). The research instrument is student worksheets (LKPD). The data sources for the study are the results of observations in class, interviews with Mathematics teachers, and students. The results of the study showed that increasing understanding of multiplication of whole numbers using the Problem Basic Learning (PBL) model got good and quite satisfactory results. So it is in accordance with what the teacher expected. In the pre-action cycle, only 1 student completed it and 12 students did not complete it, while in cycle II, 13 students completed it. Overall